Higher periprosthetic fracture rate associated with use of modern uncemented stems compared to cemented stems in femoral neck fractures. Issue 2 (March 2019) - Song, Jin Soo A.; Dillman, Daryl; Wilson, Dave; Dunbar, Michael; Richardson, Glen
Introduction: Hemiarthroplasty is the preferred treatment for displaced femoral neck fractures in elderly patients. Recently, short tapered-wedge cementless stems have increasingly been used in this population. However, historic data has consistently shown higher rates of periprosthetic fracture with uncemented stems in hip fracture patients. This study aims to evaluate the rate of periprosthetic fracture requiring re-operation and all-cause mortality between cemented and uncemented femoral stem designs including more recent short tapered-wedge cementless stems in hip fracture patients. Methods: A retrospective chart and radiographic review of patients received bipolar hemiarthroplasty for femoral neck fractures from 2010–2016. Patients biologically (age ≥ 65 years) or physiologically (American Society of Anesthesiologists (ASA) class ≥ 3) elderly were eligible. The uncemented group was subdivided into tapered-wedge stems (a broach only system) and reamed uncemented stems. The primary outcome was periprosthetic fracture requiring re-operation. Results: We included 657 patients in total, with 296 and 361 patients in the uncemented and cemented stem groups respectively. In the uncemented group there were 197 tapered-wedge and 99 reamed uncemented stems. There was a significantly higher rate of periprosthetic fracture requiring re-operation in the uncemented group (3.0% vs. 0.6%) ( p ≤ 0.05). There were no significant differences in rates of all-cause mortality, infection or all-cause re-operation. Conclusions: Compared to modern uncemented femoral stem designs, cemented stems yield lower rates of periprosthetic fracture requiring re-operation, without increasing risk of all-cause mortality. Tapered-wedge stems had similar rates of re-operation due to periprosthetic fracture as reamed uncemented stems.